2018
DOI: 10.1021/acsphotonics.8b00197
|View full text |Cite
|
Sign up to set email alerts
|

UV Soliton Dynamics and Raman-Enhanced Supercontinuum Generation in Photonic Crystal Fiber

Abstract: Ultrafast broadband ultraviolet radiation is of importance in spectroscopy and photochemistry, since high photon energies enable single-photon excitations and ultrashort pulses allow time-resolved studies. Here we report the use of gas-filled hollow-core photonic crystal fibers (HC-PCFs) for efficient ultrafast nonlinear optics in the ultraviolet. Soliton self-compression of 400 nm pulses of (unprecedentedly low) ~500 nJ energies down to sub-6-fs durations is achieved, as well as resonant emission of tunable d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The main reasons are because they offer a weak anomalous dispersion which compensates the normal dispersion of the filling gas, but more importantly they can tolerate extremely high terawatt levels of peak power due to low modal overlap with the silica cladding. Many impressive feats have been demonstrated in hollow core fibers, such as tunable and broadband DUV/Vacuum UV light generation by tuning the gas pressure inside the fiber 14 , 15 , 22 26 , four-wave mixing 27 , pulse compression in the mid-IR 28 , Raman effects 29 31 and multistage generation of extreme UV by tapering of HC-ARF 32 . Most of the experimental papers so far report on pumping a gas-filled HC-ARF in the visible and near-infrared regime close to the zero-dispersion wavelength (ZDW) of the fiber.…”
Section: Introductionmentioning
confidence: 99%
“…The main reasons are because they offer a weak anomalous dispersion which compensates the normal dispersion of the filling gas, but more importantly they can tolerate extremely high terawatt levels of peak power due to low modal overlap with the silica cladding. Many impressive feats have been demonstrated in hollow core fibers, such as tunable and broadband DUV/Vacuum UV light generation by tuning the gas pressure inside the fiber 14 , 15 , 22 26 , four-wave mixing 27 , pulse compression in the mid-IR 28 , Raman effects 29 31 and multistage generation of extreme UV by tapering of HC-ARF 32 . Most of the experimental papers so far report on pumping a gas-filled HC-ARF in the visible and near-infrared regime close to the zero-dispersion wavelength (ZDW) of the fiber.…”
Section: Introductionmentioning
confidence: 99%
“…The same group also demonstrated the shortest optical wavelength in a SC generated to date, from 124nm-1200nm using Raman active hydrogen-filled HC PCF [99]. However, all these results from HC PCFs so far have used fs input pulses with µJ pulse energies (with the exception of a recent paper [100] using 500nJ pulse energy), which sets the source requirements quite high and with very low repetition rates in the kHz making time-resolved imaging very slow. Less stringent source requirements would open the door for widespread use, especially if MHz repetition rates and high average powers could be achieved in the deep UV to IR range.…”
Section: A Uv Generationmentioning
confidence: 99%
“…They can accommodate extremely large pulse energies and higher peak-power fs pulses in the fiber, unlike solid core PCFs which would undergo optical damage [99]. Recent advances in gasfilled HC-PCFs with versatile control of dispersion and nonlinearity can allow generating more stable SC [100]. Numerical simulations have shown that the generated dispersive wave pulses in these fibers are highly coherent and independent of input pulse energy when the pulse durations are tens of fs [91].…”
Section: Stability With Greater Output Powersmentioning
confidence: 99%
“…The generation of ultra-broadband supercontinuum (SC) has been a hot topic as its favorable implications in photochemistry and spectroscopy, etc. [1,2]. The dynamics of a dispersive wave (DW) and optical soliton play an essential role in the process of SC generation.…”
Section: Introductionmentioning
confidence: 99%